PEMBERDAYAAN KELUARGA MISKIN DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - ", Nurefni; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Kuok Kuok District of Kampar. The purpose of this study was to determine who the poor population who receivedassistance from the program pemberdayaandanuntukmengetahui How the implementation of the empowerment of poor families in the village of Kuok Kuok District of Kampar. This study titled "Village PemberdayaanMasyarakatMiskindi Kuok Kuok District of Kampar". Topics focus of this research is Who Poor residents who receive assistance from the empowerment and How the implementation of empowerment of poor families in the village of Kuok Kuok District of Kampar. The subject of this research is in the village seluruhkeluargamiskin Kuok. Subject is numbered 10 poor families in Dea Kuok. The author uses descriptive qualitative method and the data were analyzed qualitatively. Instrument Data is observation, interviews and documentation. Assistance received very helpful informant informant household economy to meet the needs of sending their children ranging from elementary, junior high, high school and up keperguruan. However, there are some people who failed in perkebunandisebabkanolehhama. Agriculture caused by pests, edible ungags, and they rarely follow counseling because they are held by the government, with seeds, fertilizers and outreach to the community, help them biased produce satisfactory results.Keywords: empowerment society, Poverty and government